The Influence of Microclimate on Architectural Design in The Coastal Area, North Jakarta - Sari, Pawitra; Pradini, Purnama Sakhrial; Bomo, Desta Promesetiyo (Sinektika: Jurnal Arsitektur, 2025)
The microclimate has an influence on architectural design in order to produce thermal comfort. This study aims to evaluate the influence of microclimate on the architectural design of JIS, which is not far from Ancol Beach, especially wind speed. The method used is qualitatively descriptive. The result of the “wind environment study” is planting vegetation as an open space design in the concourse to reduce the high wind speed. Orientation on gate opening spreads flat across the side to optimize audience capacity. The orientation on the JIS mass slope is west-east, known as the west ramp because it has a strategic point as the entrance pedestrian walk and the east ramp as the exit pedestrian walk. On the facade, JIS has “a hole-hole design” with the primary function of air circulation to maximize the comfort of supporters in the stadium building. The building materials used are local materials, recycled materials, like legal wood products, and health-friendly materials. The albedo value calculated for the roof hardening area is 0.65, and for the non-roof hardening area, it is 0.40. The selection of materials is close to bright colors. The stadium roof frame, a construction system greatly influenced by wind, is designed using rules or mathematical formulas (parameters), making it a parametric design that simultaneously enhances aesthetic value. The implementation of the rooftop photovoltaic system at JIS serves to utilize sunlight as an energy-saving measure.